Prognostic role and predictors of high Killip class in myocardial infarction with non-obstructive coronary artery. (3rd October 2022) - Impellizzeri, A; Amicone, S; Armillotta, M; Sansonetti, A; Stefanizzi, A; Angeli, F; Fabrizio, M; Bodega, F; Canton, L; Tattilo, F P; Bergamaschi, L; Foa', A; et al.
Abstract: Background: Killip classification is a simple clinical tool for risk stratification in patients with acute myocardial infarction (AMI). However, predictors of high Killip class at admission and its prognostic role in myocardial infarction with non-obstructive coronary artery (MINOCA) are still poorly explored. Purpose: To identify clinical predictors of high Killip class and its potential prognostic role in patients with MINOCA compared to patients with myocardial infarction with obstructive coronary artery (MIOCA). Methods: We included patients with AMI undergoing coronary angiogram from January 2016 to June 2021. MINOCA were defined according to the current European guidelines criteria. We compared the Killip classes of MINOCA with those of MIOCA and defined a high Killip class if greater than 1. Kaplan-Meier (KM) curves were developed for the comparison of all-cause mortality among MIOCA and MINOCA with high Killip class (>1) compared to the others. Multivariate logistic regression analysis was used to determine the predictors of high Killip class. Results: Among 3261 AMI, 261 were MINOCA. The median follow-up time was 36.1±15.2 months. Killip class >1 occurred in 24 (8.8%) MINOCA patients compared to 518 (17.3%) MIOCA cases (p=0.001). During long-term follow-up, a high Killip class was associated with a 3-fold increased mortality both in MIOCA and MINOCA populations (p<0.001 and p=0.001). Furthermore, in both groups, the KM survival curves were significantly worse for patients with high Killip class compared to lower classes (p<0.001). Within MIOCA multivariate logistic regression showed that predictors of a high Killip class at admission were older age [OR 1.04, 95% CI (1.03–1.06), p<0.001], diabetes [OR 1.60, 95% CI (1.24–2.07), p<0.001], ST-segment-elevation [OR 1.53, 95% CI (1.12–2.10), p=0.008], left ventricular ejection fraction (LVEF) [OR 0.95, 95% CI (0.94–0.96), p<0.001] and elevated cardiac troponin [OR 1.01, 95% CI (1.00–1.01), p=0.01]. Instead, in MINOCA only older age [OR 1.08, 95% CI (1.03–1.14), p=0.003], ST-segment-elevation [OR 7.40, 95% CI (1.08–50.65), p=0.04] and diabetes [OR 3.60, 95% CI (1.09–11.96), p=0.04] were predictors of a high Killip class whereas LVEF (p=0.3) and elevated cardiac troponin (p=0.6) exhibited a neutral impact in these patients. Conclusions: High Killip class at admission is a high-risk marker of adverse cardiovascular events even in patients with MINOCA. Simple baseline characteristics (such as older age, diabetes, ST-segment-elevation) predict a high Killip class in MINOCA subjects and can help to identify a high-risk population who might benefit from a stricter management. Furthermore, LVEF and elevated cardiac troponin were identified as predictors of a high Killip class in MIOCA but they did not show a similar impact in the setting of MINOCA. This may reflect the different pathogenesis and myocardial damage extent in MINOCA compared to MIOCA. Funding Acknowledgement: Type of funding sources: None.